1994
DOI: 10.1037/0022-3514.66.4.776
|View full text |Cite
|
Sign up to set email alerts
|

The relations of emotionality and regulation to dispositional and situational empathy-related responding.

Abstract: The purpose of the present study was to examine the prediction of adults' situational and dispositional empathy-related responses from measures of emotionality (emotional intensity and positive and negative affect) and regulation. A multimethod approach including self-reported, facial, and heart rate (HR) responses was used to assess situational vicarious emotional responding; Ss' (and sometimes friends') reports were used to assess the dispositional characteristics. In general, dispositional sympathy, persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
409
2
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 490 publications
(442 citation statements)
references
References 64 publications
23
409
2
8
Order By: Relevance
“…A potential key process might be the ability to regulate this self-oriented distress elicited by viewing another's pain 8,34,36 . In the present study, observers' distress is likely an automatic response to another's pain, which in later stages may be regulated by contextual and individual difference variables 32,35 , enabling other-oriented emotions to prevail 22,30,35,72,77 51 , it would be interesting to replicate the findings in participants with a close relationship, e.g. couples or parent-child dyads.…”
Section: Self-report Datamentioning
confidence: 77%
“…A potential key process might be the ability to regulate this self-oriented distress elicited by viewing another's pain 8,34,36 . In the present study, observers' distress is likely an automatic response to another's pain, which in later stages may be regulated by contextual and individual difference variables 32,35 , enabling other-oriented emotions to prevail 22,30,35,72,77 51 , it would be interesting to replicate the findings in participants with a close relationship, e.g. couples or parent-child dyads.…”
Section: Self-report Datamentioning
confidence: 77%
“…The findings also suggest that individual differences in the development of EC predict sympathy in early to mid adolescence. Individuals who respond with emotion to others' plight but cannot modulate their emotional arousal are believed, and have been found, to experience personal distress, at least in evocative situations in which empathic individuals would be expected to experience relatively high levels of vicariously induced negative emotion (Eisenberg et al, 1994.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that children who are impulsive are less inhibited about reporting sympathy and/or more likely to acknowledge their emotional experience. Adults who are somewhat emotional, even if they are well regulated, are relatively likely to experience or report sympathy (e.g., Eisenberg et al, 1994). However, this explanation is speculative and should be tested further.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, results of several empirical studies indicate that emotional reactivity and regulation act jointly (e.g., Eisenberg et al, 2001Eisenberg et al, , 1993 Eisenberg, Guthrie et al, 1997; Eisenberg, Fabes et al, 1997;Fabes et al, 1999;Rothbart, Ahadi, & Hershey, 1994). For example, Eisenberg et al (1996) reported that first to third grade children who were high in negative emotionality and low in regulation were prone to externalizing behavior problems, with the effect of regulation being stronger for those high in negative emotionality. Likewise, Eisenberg et al (1993) found that high emotional intensity and low (attention) regulation were associated with low social skills and low sociometric (peer) status in preschool children.…”
Section: Introductionmentioning
confidence: 99%